Willingness to take risk: The role of risk conception and optimism - Thomas Dohmen; Simone Quercia; Jana Willrodt (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We show that the disposition to focus on favorable or unfavorable outcomes of risky situations affects willingness to take risk as measured by the general risk question. We demonstrate that this disposition, which we call risk conception, is strongly associated with optimism, a stable facet of personality, and that it predicts real-life risk taking. The general risk question captures this disposition alongside pure risk preference. This likely contributes to the predictive power of the general risk question across domains. Our results also rationalize why risk taking is related to optimism.
Keywords: D91; C91; D81; D01; 330; risk taking behavior; optimism; preference measure; risk conception